Quantized Fuzzy Cooperative Output Regulation for Heterogeneous Nonlinear Multiagent Systems With Directed Fixed/Switching Topologies - Dong, Shanling; Liu, Lu; Feng, Gang; Liu, Meiqin; Wu, Zheng-Guang (IEEE transactions on cybernetics, 2022)
This article investigates the cooperative output regulation problem for heterogeneous nonlinear multiagent systems subject to disturbances and quantization. The agent dynamics are modeled by the well-known Takagi-Sugeno fuzzy systems. Distributed reference generators are first devised to estimate the state of the exosystem under directed fixed and switching communication graphs, respectively. Then, distributed fuzzy cooperative controllers are designed for individual agents. Via the Lyapunov technique, sufficient conditions are obtained to guarantee the output synchronization of the resulting closed-loop multiagent system. Finally, the viability of proposed design approaches is demonstrated by an example of multiple single-link robot arms.